Instrument of glossary: the effects of its use in learning islamic thought and civilization at UiTM kelantan / Nor Asmira Mat Jusoh ...[et al.]. - Mat Jusoh, Nor Asmira; Noor Zainan, Nurul Izzah; Awang @ Ab. Rahman, Nurul Hidayah; Tasir, Siti Fatimah; Mustafa@Busu, Zanirah (Global Academic Excellence, 2018)
Islamic Thought and Civilization (CTU151) is a compulsory course to be taken by all students in the Part 2 diploma program at UiTM. This course explains the concept of the Islamic civilization and its contribution to the world's civilization, the Islam in the Malay world, the family system, the national and civil community in Islam, as well as the challenges faced by the current Muslim world (CITU Course Description UiTM). The results showed that students have difficulties in mastering this subject based on the results in CTU151 courses in each semester which shows that the level of student achievement was at the intermediate level. To overcome these problems, the lecturers of Academy of Contemporary Islamic Studies (ACIS) UiTM Kelantan Branch has introduced the use of the glossary to enable the students to understand and master the subject. The present study used quantitative methods, namely by distributing questionnaires on the use of glossary in learning to all students in the diploma program Part 2 (2017/2018) at UiTM Kelantan branch. From 254 subjects, a total of 162 questionnaires were completed. The data from the questionnaires were analyzed using SPSS version 24.0 using t-test, ANOVA and correlation analysis. Results showed that several factors are involved in determining the level of understanding of students in the Islamic thought and civilization course. The present study benefits the students in understanding and mastering the subject better, thus fulfilling the learning needs in the present time.